2012
DOI: 10.1111/j.1528-1167.2012.03409.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the permeability and P‐glycoprotein efflux of carbamazepine and several derivatives across mouse small intestine by the Ussing chamber technique

Abstract: SUMMARYPurpose: The rational discovery and development of new antiepileptic drugs (AEDs) with safer therapeutic index and better pharmacokinetic properties is still warranted nowadays. Because the long-term management of epilepsy is attained by means of orally administered AEDs, investigation of their potential to be well absorbed at the intestinal level is mandatory. Moreover, involvement of the efflux transport mediated by P-glycoprotein (P-gp) may compromise the systemic and central nervous system dispositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Mucosal atrophy could result in greater epithelial permeability and impair barrier function, and lead to bacterial translocation and subsequent sepsis (Sun et al, 2006). The increased propranolol permeability and decreased Rho123 permeability, which indicated increased passive transcellular transport and decreased P-gp dependent efflux transport (Fortuna et al, 2012), suggested that the intestinal membrane viability was decreased and P-gp function was impaired. Moreover, increased plasma endotoxin levels were observed when chicks fed with basal diet were challenged with C. perfringens, which might result from overgrowth of gram-negative bacteria (particularly E. coli), and bacteria and endotoxin translocation into organs and blood circulation (Collier et al, 2008;Liu et al, 2010Liu et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucosal atrophy could result in greater epithelial permeability and impair barrier function, and lead to bacterial translocation and subsequent sepsis (Sun et al, 2006). The increased propranolol permeability and decreased Rho123 permeability, which indicated increased passive transcellular transport and decreased P-gp dependent efflux transport (Fortuna et al, 2012), suggested that the intestinal membrane viability was decreased and P-gp function was impaired. Moreover, increased plasma endotoxin levels were observed when chicks fed with basal diet were challenged with C. perfringens, which might result from overgrowth of gram-negative bacteria (particularly E. coli), and bacteria and endotoxin translocation into organs and blood circulation (Collier et al, 2008;Liu et al, 2010Liu et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The passive transcellular transport marker and P-glycoprotein (P-gp) dependent efflux transport marker (propranolol and Rhodamine 123 (Rho123), respectively) were assessed to investigate intestinal membrane viability and P-gp transporter functionality (Fortuna et al, 2012). Propranolol permeability was investigated in mucosal to serosal direction (M-S), while Rho123 was assessed from serosa to mucosa (S-M).…”
Section: Intestinal Barrier Integrity and Functionmentioning
confidence: 99%
“…The Ussing Chamber protocol was adapted from a published method (Oga et al, 2013;Fortuna et al, 2012). Rats were sacrificed by cervical dislocation and the entire small intestine was rapidly removed, stored in the Krebs-Ringer buffer (KRB) solution, composed of 115 mM NaCl, 25 mM NaHCO 3 , 2.4 mM K 2 HPO 4 , 1.2 mM CaCl 2 , 1.2 mM MgCl 2 , 0.4 mM KH 2 PO 4 , and 10 mM D-glucose, pH7.4 saturated with carbogen (95% O 2 , 5% CO 2 ).…”
Section: Ussing Chamber Preparationmentioning
confidence: 99%
“…Calcium channel blockers are being used to reduce that drug efflux by interference with P-gp function in intestinal wall and in the apical membrane of brain capillary endothelial cells of the blood-brain barrier [11]. The most commonly calcium antagonist used to block the P-gp protein is Verapamil [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, there is increasing evidence that drug efflux transporters (namely P-gp protein [P-glycoprotein] and MDRP [multidrug resistant protein] may play a role in drug-resistant epilepsy by limiting gastrointestinal absorption and brain access of antiepileptic drugs [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%